Identification of gene functions associated to active and dormant buds in Arabidopsis - González-Grandío, Eduardo (Landes Bioscience, 2014)
In Arabidopsis, axillary buds may become dormant in response to a far-red rich light or to increased apical dominance. BRANCHED1 (BRC1) is required for this response. Transcriptional profiling studies of wild-type and brc1 mutant buds allowed the identification of sets of BRC1-dependent genes including a group of ABA-related genes upregulated in dormant buds. By using BRC1 inducible lines we demonstrate that 2 of these ABA response factors, ABF3 and ABI5, are positively regulated in axillary buds by BRC1 after induction. To get further insight into the genetic control of the growth-to-dormancy transition in buds we have also compared this transcriptomic data with 2 additional “active vs dormant bud” transcriptomic data sets and found “core” co-regulated gene networks tightly associated to each condition.